Suggestions for changing professional ethics educational system - Seyyed Hatam Mahdavinoor; Azam Jadidi Miandashti; Seyyed Muhammad Mahdi Mahdavinoor (Tabriz University of Medical Sciences, 2021)
Background: Professional ethics is of great importance in health-related fields, and observation of professional ethics by the treatment staff will lead to increased patient satisfaction. Legislators have attempted to improve adherence to professional ethics by compiling codes of ethics and holding professional ethics classes in universities. Despite these efforts to develop such codes of ethics, treatment staff do not always fully comply with professional ethics, leading to decreases in patient satisfaction. Methods: Based on the authors' experiences and related studies, we present several suggestions for improving the observation of professional ethics among treatment staff. Results: Strategies that can help improve ethical-behavioral patterns among treatment staff are as follows: Changing university entrance examinations, increasing professional ethics credits, teaching ethics regardless of religion, teaching the history of medicine, logotherapy of students during their university years, training in psychology as the core of medical education programs, and reformulating the incentive and punishment system. Conclusion: It is required to make specific changes in the selection method and training of treatment staff to enhance client satisfaction. These recommendations are given according to the health system of Iran, but they can also be used in other countries.